Pemeriksaan T4 dan TSH dalam Deteksi Dini Hipotiroidisme Kongenital pada Bayi Baru Lahir: Apa Dilemanya? - Mashabi, Yasmine (Fakultas Kedokteran Universitas Trisakti, 2024)
Untreated congenital hypothyroidism (CH) leads to intellectual disability. Newborn screening (NBS) for CH should be done on all infants. Prompt diagnosis by NBS leads to early and adequate treatment outcomes in very normal neurocognitive outcomes in adulthood. Newborn screening (NBS) for congenital hypothyroidism (CH) is one of the major achievements in preventive medicine. Most neonates born with CH have a normal appearance and no detectable physical signs. Blood spot thyroid stimulating hormone (TSH), thyroxine (T4), or both can be used for CH screening. The latter is more sensitive but not cost-effective, so screening by TSH or T4 is used in various programs worldwide. TSH screening is more specific in the diagnosis of CH. T4 screening is more sensitive in detecting newborns with rare hypothalamic-pituitary-hypothyroidism, but it’s less specific with a high frequency of false positives especially in low birth weight and premature infants. NBS alone is not sufficient to prevent adverse outcomes from CH in a pediatric population. In addition to NBS, the management of CH requires timely confirmation of the diagnosis and accurate interpretation of thyroid function testing, effective treatment, and consistent follow-up. Doctors need to consider hypothyroidism in the face of clinical symptoms, even if NBS thyroid test results are normal. When clinical symptoms and signs of hypothyroidism appear (such as large posterior fontanelles, large tongue, umbilical hernia, prolonged jaundice, constipation, lethargy, and/or hypothermia), measurement of serum thyroid hormone and free thyroxine is indicated, regardless of NBS results. So all these babies should be treated as having CH during the first 3 years of life, taking into account the risk of mental retardation. Re-evaluation after 3 years is required in such patients.